Teknik penyajian presentasi ilmiah yang efektif dengan menggunakan media elektronik - Elizabeth Mailoa (DiscoverSys Inc., 2008)
The digital era has transformed the manner in which scientific material is presentedto dental professional. With recent technological advances, speakers presentinginformation have greater options to deliver their materials. Most notably, speakersare able to use media to assist and enhance presentations. Recent technology ofpresentations with software such as PowerPoint has becoming popular lately, becausethis software has many advantages, such as the ability to incorporate graphics, textand sound in a multimedia files. An effective presentation is when your audience caneasily grasp the ideas you are trying to get across. In scientific presentationsengaging and clear visuals complement the speaker role of translating andcommunicating information. Scientific presentation with projecting images and teststimulates audience attention and retention. The purpose of this article is to providekey points on in focus in the delivery of presentation, and to maximize its effectivenessby using the benefit of electronic digital media.